Pengaruh Model Pembelajaran Problem Based Learning terhadap Peningkatan Hasil Belajar Siswa Kelas VIII UPT SMP Negeri 4 Takalar - Muh. Risal; A. Khairah Yukhlifah S; Muhammad Dahlan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Conventional learning often shows ineffectiveness in improving student learning outcomes on the topic of the human respiratory system in grade VIII, mainly due to low student motivation and engagement in the learning process. Therefore, the Problem-Based Learning (PBL) model is proposed as an innovative alternative. This study aims to examine the effect of implementing the PBL model on improving student learning outcomes in grade VIII B of UPT SMP Negeri 4 Takalar. Adopting a quasi-experimental approach with a non-equivalent control group pretest-posttest design, the study involved 26 students who were divided equally into an experimental group (13 students implementing PBL) and a control group (13 students with a conventional approach). Data collection was carried out through learning outcome tests and observations of student activities, then analyzed using a t-test. The findings revealed that the average posttest score of the experimental group reached 85.67, significantly higher than the control group at 75.84, with a p value <0.05 indicating a significant effect of PBL. The research conclusion states that PBL is effective in increasing understanding of the concept of the human respiratory system, in line with the principles of the Independent Curriculum, so it is recommended for widespread application in school environments.